Fairy tales and abandonment between symbolism and reality: persistence and rewritings - Chiara Lepri (Firenze University Press, 2022)
Starting from a reflection on the motif of abandonment in the fairy tale, this paper intends to investigate its persistence in modern and contemporary children's literature, with particular reference to rewritings and revisitations of classical fairy tales through the special textuality of the picture book. Abandonment thus becomes a key concept, among many others, to retrace in a historiographical perspective the plots of a lost childhood that from ancient times comes down to us between persistences and distortions that update its meaning.